FIFTEEN YEARS AFTER THE ZAPATISTA UPRISING: SUCCESSES AND CHALLENGES OF A LOCAL MOVEMENT IN THE GLOBAL AGE - Pleyers, Geoffrey (2013)
This article proposes a balance of the Zapatista movement considered as a “movement of experience”. While their impact on Mexican policies has been limited, the Zapatista have managed to build autonomous spaces where they implement alternative forms of collective organizations and social relations. Their communities have undergone a process of deep change based on two core values of the Zapatista movement: dignity and autonomy. However, the will that the movement is based on strong local roots and on a process of local transformation, it does not mean that its challenges are limited to the local level. Their struggle is properly universal and global, but they consider the development of alternative practices at the local level to be the key element of any global change. The Zapatista movement relies thus on a complex combination between two distinct trends: one focuses on the building of local autonomy while the other remains very active on the national and international social and political arena.